(untitled) (Cadernos de Sociomuseologia, 2016)
The present dissertation supports the hypothesis that the processes of research, preservation and communication of the operational museological chain involved in the conception of long term exhibitions and program of actions of museums and memorials related to the theme of Holocaust promote the realization of the social function of museums ln contemporary society, once they constitute a tool of knowledge, education and mobilization in service of the development of critical and more socially responsible individuals and of the diffusion of a culture of peace, overcoming racism, discrimination and intolerance, and human rights preservation. The dissertation presents the Holocaust Museum of Curitiba as a case study, a cultural and educational institution dedicated to researching, preserving and communicating the memory and history of the Holocaust. Keywords: Human Rights; Holocaust; Memory; Musealization; Holocaust Museum of Curitiba